2018
DOI: 10.1097/spv.0000000000000646
|View full text |Cite
|
Sign up to set email alerts
|

Indwelling Versus Immediate Removal of Transurethral Catheter After Robotic Sacrocolpopexy: A Randomized Clinical Trial

Abstract: Introduction and Hypothesis This study evaluates the necessity and effect of an indwelling transurethral catheter in the early postoperative period following a robotic-assisted laparoscopic sacrocolpopexy. Methods This was a randomized clinical trial of patients who underwent a robotic sacrocolpopexy for pelvic organ prolapse. Patients were randomized to have their transurethral catheter removed 6 hours postoperative (intervention group) or the morning … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
13
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 25 publications
0
13
0
1
Order By: Relevance
“…Eight reports were not retrieved, resulting in 102 articles being assessed for eligibility. A total of 20 studies were included in this systematic review (Figure 1), including 13 randomised controlled trials (Ahmed et al, 2014;Aref, 2020;Atilgan et al, 2020;Chai & Pun, 2011;Dunn et al, 2003;El-Mazny et al, 2014;Joshi et al, 2014;Liang et al, 2009;Onile et al, 2008;Ouladsahebmadarek et al, 2012;Sandberg et al, 2019;Sekhavat et al, 2008;Vallabh-Patel et al, 2020) and seven uncontrolled studies (Campbell et al, 2017;Dedden et al, 2020;Duchalais et al, 2019;Hung et al, 2020;Karp et al, 2018;Mengatto et al, 2020;Yoo et al, 2015). Reasons for exclusion were as follows: (a) the use of perioperative epidural anaes-…”
Section: Study Selectionmentioning
confidence: 99%
See 2 more Smart Citations
“…Eight reports were not retrieved, resulting in 102 articles being assessed for eligibility. A total of 20 studies were included in this systematic review (Figure 1), including 13 randomised controlled trials (Ahmed et al, 2014;Aref, 2020;Atilgan et al, 2020;Chai & Pun, 2011;Dunn et al, 2003;El-Mazny et al, 2014;Joshi et al, 2014;Liang et al, 2009;Onile et al, 2008;Ouladsahebmadarek et al, 2012;Sandberg et al, 2019;Sekhavat et al, 2008;Vallabh-Patel et al, 2020) and seven uncontrolled studies (Campbell et al, 2017;Dedden et al, 2020;Duchalais et al, 2019;Hung et al, 2020;Karp et al, 2018;Mengatto et al, 2020;Yoo et al, 2015). Reasons for exclusion were as follows: (a) the use of perioperative epidural anaes-…”
Section: Study Selectionmentioning
confidence: 99%
“…& Pun, 2011;Dunn et al, 2003;Joshi et al, 2014;Liang et al, 2009;Sandberg et al, 2019;Vallabh-Patel et al, 2020).…”
unclassified
See 1 more Smart Citation
“…Both studies utilized active voiding trials. One RCT found that women who had their catheter removed 6 hours after the robotic ASC were more likely to have urinary retention and UTI compared to women who underwent removal on postoperative day one 35 . Another study of women undergoing pelvic organ prolapse surgery, where the most common procedure was laparoscopic or robotic ASC, investigated whether removing the Foley was possible at 4 hours postoperatively.…”
Section: Resultsmentioning
confidence: 99%
“…One RCT found that women who had their catheter removed 6 hours after the robotic ASC were more likely to have urinary retention and UTI compared to women who underwent removal on postoperative day one. 35 Another study of women undergoing pelvic organ prolapse surgery, where the most common procedure was laparoscopic or robotic ASC, investigated whether removing the Foley was possible at 4 hours postoperatively. They found the early catheter removal led to decreased time to first spontaneous void, and no significant differences in UTIs, although the sample size was not powered to detect differences.…”
Section: Urinary Drainagementioning
confidence: 99%